2018
DOI: 10.1111/inm.12452
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the current sexual health service provision for mental health consumers by nurses in mental health settings: Findings from a Survey in Australia and England

Abstract: Nurses in mental health settings avoid talking to consumers about sexual health concerns. It is unclear whether this avoidance prevents the provision of sexual healthcare. The present study gathered information about how mental health nurses respond to sexual health issues within their routine practice, what issues they address, and their view on their role in promoting sexual health for consumers. A cross-sectional study using an electronic survey questionnaire, originally generated from a previous study in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…( M = 14.9)Routine practice.ServiceCommon reference to: sexual function assessment, psychotropic side-effects, patient embarrassment, and pros and cons of information. Sexual side effects recognised as impacting on medication adherence but most did not discuss it with patients.Quinn et al [60] [Not stated]Uk & AustraliaCross-sectional survey. Sexual health care/Purpose-designed survey questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…( M = 14.9)Routine practice.ServiceCommon reference to: sexual function assessment, psychotropic side-effects, patient embarrassment, and pros and cons of information. Sexual side effects recognised as impacting on medication adherence but most did not discuss it with patients.Quinn et al [60] [Not stated]Uk & AustraliaCross-sectional survey. Sexual health care/Purpose-designed survey questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…Byers 2011;Nnaji & Friedman 2008;Reissing & Di Giulio 2010;Rele & Wylie 2007). Reported barriers to addressing sexuality in mental health settings also appear to be consistent across nursing, psychology, and psychiatry; these include discomfort with the topic, a lack of time to address sexual concerns, and a dearth of appropriate pre-registration and continuing education (e.g., Hendry et al 2018;Quinn et al 2018;Reissing & Di Giulio 2010).…”
Section: Introductionmentioning
confidence: 95%
“…), do not routinely include aspects of sexuality in their work (Quinn et al . ), and inadvertently engage a range of strategies to silence sexuality within the therapeutic encounter (Higgins et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were echoed in a survey of mental health staff in England and Australia about sexual health provision. 25 Participants from both countries reported that very limited sexual health work was being undertaken in routine practice but they did see it as part of their role. Therefore, in order to address this issue, mental health staff require training and guidance in relation to sexual health issues in SMI and in how to engage people in conversations about sexual behaviour, and offer advice about where to access help for contraception and sexual health concerns.…”
Section: Mental Health Service Response To Sexual Healthmentioning
confidence: 99%